A round robin test for total reflection X-ray fluorescence analysis using preselected and well characterized samples. Issue 9 (29th July 2021) - Unterumsberger, Rainer; Beckhoff, Burkhard; Gross, Armin; Stosnach, Hagen; Nowak, Sascha; Stenzel, Yannick P.; Krämer, Markus; von Bohlen, Alex
Abstract : A TXRF round robin test using preselected micro- and nanoscaled samples has been performed and shows excellent results, demonstrating the strength and reliability of the TXRF method when decoupled from unfavorable sample preparations. Abstract : In this work, we present the results of the first round robin test of different kinds of micro- and nanoscaled samples for total reflection X-ray fluorescence (TXRF) analysis. Therefore preselected, well-characterized samples including an internal standard were provided to the participants of the round robin test. Three different kinds of samples were produced ensuring highly homogeneous mass depositions: first, manually produced μL droplets, representing the most common sample preparation in TXRF. Second, nL droplets pipetted with a nL dispenser, having the potential of being μL (total volume) samples distributed in an optimized manner with respect to reproducibility and homogeneity. Third, multi-elemental sub-monolayers, coated over the entire sample surface, simulating surface contamination and thereby representing ideal samples for the TXRF method. One of the several elements coated as sub-monolayers was selected as an internal standard and quantified with physically traceable XRF. The approach for an accurate and precise round robin activity was to separate the influence of the TXRF instrumental response and internal standard based quantification from any impact related to the sample preparation, in particular spatial inhomogeneity revealed by different X-ray spectrometric techniques. The results of the round robin test are in line with expectations and lie within about 5% deviation for all droplets and about 3% for the layers, showing the strength and reliability of the TXRF method for simultaneous multi-element analysis when decoupled from unfavorable sample preparations. For validation purposes, physically traceable XRF quantification was performed for one selected sample, and the absolute mass deposition of the respective elements was determined.